2018
DOI: 10.1093/aobpla/ply022
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the degree of reciprocal herkogamy affects the degree of legitimate pollination in a distylous species

Abstract: Distyly is a widespread floral polymorphism characterized by the flowers within a population showing reciprocal placement of the anthers and stigma. Darwin hypothesizes that distyly evolves to promote precise pollen transfer between morphs. Primula chungensis exhibits two types of anther heights, and these two types of anthers show pollen of two different size classes. To understand whether the stigma could capture more pollen grains from the anthers of the pollen donor as the separation between the stigma of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Further analysis revealed that the average seed set rate via selfing was relatively high (> 0.55 for all herkogamy classes; Figure 8 ) and showed no significant difference among herkogamy classes with separation less than 1.0 mm; however, the seed set rate sharply decreased to less than 0.10 with an increase in separation ( Figure 8 ). This sharp decline in the seed set rate could be explained based on the assumption that the HE value of 1.0 mm possibly represents an approximate threshold, consistent with previous studies on the homostylous species P. halleri ( de Vos et al, 2014 , 2018 ) and distylous species Primula chungensis ( Jiang et al, 2018 ), suggesting that this threshold likely has wider applicability, although experimental confirmation is needed.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Further analysis revealed that the average seed set rate via selfing was relatively high (> 0.55 for all herkogamy classes; Figure 8 ) and showed no significant difference among herkogamy classes with separation less than 1.0 mm; however, the seed set rate sharply decreased to less than 0.10 with an increase in separation ( Figure 8 ). This sharp decline in the seed set rate could be explained based on the assumption that the HE value of 1.0 mm possibly represents an approximate threshold, consistent with previous studies on the homostylous species P. halleri ( de Vos et al, 2014 , 2018 ) and distylous species Primula chungensis ( Jiang et al, 2018 ), suggesting that this threshold likely has wider applicability, although experimental confirmation is needed.…”
Section: Discussionsupporting
confidence: 84%
“…According to our current observations, we conform this prediction, i.e., the selfing seed set rate is low and effected by herkogamy variation is very limited in central populations ( Figure 5 ), which possess a relatively strict self-incompatibility system ( Shao et al, 2019 ). However, it is largely unknown whether and to what extent the variation in herkogamy affects opportunities for autonomous selfing and reproductive assurance in heterostylous plants with self- or partially self-compatible systems, although the self-incompatibility of quite a few distylous species is not strictly ( Riveros et al, 1995 ), even in the typical distylous genus Primula ( Wedderburn and Richards, 1990 ; Barrett and Cruzan, 1994 ; Riveros et al, 1995 ; Yuan et al, 2017 ; Zhou et al, 2017 ; Jiang et al, 2018 ; Shao et al, 2019 ). In the marginal populations of P. wannanensis , self-incompatibility is fairly weak ( Shao et al, 2019 ), and we found that the degree of herkogamy directly affected the autonomous selfing capacity of plants in the absence of pollinators ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetries in pollen flow might be an important first step towards gender specialization. Here we showed that failures in pollen transfer, which deviates P. padifolia from the expected disassortative pollination in distylous plants (Darwin 1877, Lloyd & Webb 1992b, Barrett 2002, 2019, Jiang et al 2018, are potentially accompanied by major male sterility in SS flowers. Asymmetrical pollen transfer has been observed in several distylous Palicourea species, with higher percentages of compatible pollination in the LS-morph than in the SS-morph in P. fendleri (Lau & Bosque 2003) and P. tetragona (Martén-Rodríguez et al 2013), while other species (P. lasiorrachis, Feinsinger & Busby 1987;P.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the documented dissimilarities between morphs in P. padifolia should lead to differences in their abilities to gain reproductive success through female versus male function. Because P. padifolia is morphologically distylous with complete intra-morph incompatibility, the vector-mediated asymmetrical pollen transfer between morphs, which is not consistent with Darwin's hypothesis of disassortative pollination, and allocation differences between floral morphs are likely the conditions for gender specialization in distylous species and less likely selfing avoidance because intra-morphincompatibility would greatly avoid self-fertilization (see also Zhou et al 2015, Jiang et al 2018.…”
mentioning
confidence: 99%